Literatur review : Konsumsi teh hijau (Camellia sinensis) terhadap penurunan tekanan darah pada penderita hipertensi - Azizah, Mulia Fadhilatul; Rahmiwati, Anita; Novrikasari, Novrikasari (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: A patient is diagnosed with hypertension if their diastolic blood pressure regularly rises to 90 mmHg or higher on multiple examinations, and their systolic blood pressure regularly rises to 140 mmHg or higher. Tea is a functional food that has quite high antioxidant, anti-inflammatory, antimicrobial and anti-hypertensive content.Objectives: It is necessary to find out there is a connection between drinking green tea and lowering blood pressure in people with hypertension.Methods: This research uses a Systematic Literature Review with the PRISMA method. Protocol and SLR evaluation was carried out using the PRISMA method to select the research articles used. Articles obtained from Science Direct, PubMed, and Google Scholar. Keywords use English and Indonesian. Search terms in Indonesian included “green tea and blood pressure” OR “camellia sinensis and blood pressure” OR “green tea and hypertension” OR “camellia sinensis and hypertension”. Meanwhile, search terms in English include "Green Tea and blood pressure" OR "camellia sinensis and blood pressure" OR "green tea and hypertension" OR "camellia sinensis and hypertension". Based on an examination of the inclusion criteria for full text articles, open access, using quantitative methods, and publications released in 2019-2023, the final results were 7 articles used in this research.Results: It was found that consuming green tea can reduce blood pressure in people with hypertension. Regular tea consumption in hypertension sufferers can reduce systolic blood pressure by around −4,81 mmHg and reduce blood pressure by around −1,98 mmHg, with the recommendation of consuming 1-2 brews of green tea for 7 days.Conclusion: Giving green tea to people with hypertension can reduce blood pressure.